Consumption Pattern and Quality Characteristics of Tandoor / Tikka Type of Chicken Meat Product - Sen, A.R.; Reddy, G.V. Bhaskar; kumar, M. Mutu; Naveena , B.M.; A.S., Nithin; Naveena , B.M.; A.S., Nithin (Journal of Meat Science, 2019)
The present study was envisaged to assess the consumption pattern and influence of different cooking methods on quality characteristics of tandoor/tikka type of chicken meat product. A total of 112 consumers at 8 restaurants throughout Hyderabad were surveyed for consumption pattern of tandoor type muscle food based products. Most of the consumers prefer such type of product prepared from mutton. However, 43.14 % of consumers prefer chicken based and 6.86% of consumers prefer fish products. Amongst the products surveyed, 31 % consumers are preferring tandoor type of product, whereas 10% consumers mostly like tikka/kebabs type of products. The 70 % of total consumers take these types of products twice in a week. The 42.50 % of consumers are taking more than 200 gm of such products at a time. Cooking methods significantly (P
Keywords: Chicken tikka; consumption pattern; cooking methods; quality character